Internalisasi Nilai-Nilai Panca Jiwa Pesantren pada Siswa MTS Yapika Petanahan, Kebumen - Muhamad Manarul Huda; Muhamad Yusuf Amin Nugroho; Ahmad Zuhdi (Reflection : Islamic Education Journal, 2026)
This research is motivated by the importance of instilling character based on local Islamic boarding school (pesantren) values in formal educational institutions to protect students from moral degradation amid contemporary social challenges. The study aims to examine the process of internalizing the Panca Jiwa values sincerity, simplicity, self-reliance, Islamic brotherhood, and freedom among students at MTs Yapika Petanahan, Kebumen, as well as to identify the supporting factors, inhibiting factors, and impacts of their implementation. This research employed a qualitative field study approach. Data were collected through observation, interviews, and documentation and analyzed using descriptive qualitative techniques. The findings reveal that the internalization of Panca Jiwa values is carried out through habituation, role modeling (uswah hasanah), religious activities, and the integration of values into the daily culture of the madrasah. Although these values are not formally stated in the curriculum, they are consistently embedded in students’ learning experiences and social interactions. The primary supporting factor is the strong synergy between the madrasah and the surrounding pesantren environment, which creates a religious and value-oriented educational ecosystem. Meanwhile, the main obstacle is the limited interaction time experienced by students who do not reside in the pesantren. The implementation of Panca Jiwa values has a positive impact on students by strengthening discipline, fostering independence, encouraging social responsibility, and developing inclusive attitudes in everyday life.